A Review on Unmasking Merkel Cell Polyomavirus: From Discovery to Cancer Driver - Poonam; Nchang Fondah Awamofor (International Journal of Virus Studies, 2025)
Merkel cell polyomavirus (MCPyV) is a small, non-enveloped, circular double-stranded DNA virus belonging to the Polyomaviridae family, first characterized in 2008. Epidemiological data suggest widespread exposure, with seroprevalence rates approaching 80% in adults. While primary infection is typically asymptomatic, rare integration events in Merkel cells can initiate oncogenesis, yielding Merkel cell carcinoma (MCC), a neuroendocrine skin cancer with a five-year survival rate under 60%. This review integrates findings from six project chapters, spanning the viral molecular biology, host-virus interactions, clinical management, and public health strategies related to MCPyV and MCC. We detail key aspects of the viral genome, including the role of large T (LT) and small T (sT) antigens in promoting cell cycle dysregulation and inhibiting tumor suppressor pathways. Host immune surveillance, particularly T-cell and humoral responses, is explored in the context of viral persistence and immune evasion. Clinically, we discuss diagnostic approaches including serology and PCR and highlight recent advances in immunotherapy and targeted treatments for MCC. Public health efforts, such as awareness campaigns and the potential for future vaccine development, are also evaluated. By synthesizing foundational discoveries with recent advances, this review underscores the complexity of MCPyV-associated oncogenesis and identifies critical gaps in knowledge. Future research should aim to clarify mechanisms of viral integration, identify early biomarkers of malignant progression, and develop preventive interventions tailored to at-risk populations. This review integrates findings from six project chapters, covering viral molecular biology, host virus interactions, clinical management, and public health strategies. We synthesize foundational discoveries with recent advances, identify knowledge gaps, and propose directions for future research to inform diagnostics, therapeutics, and preventive interventions.
Keywords: Merkel cell carcinoma (MCC); Merkel cell polyomavirus (MCPyV); immunotherapy; oncogenesis; viral integration